(untitled) (Revista Rupturas, 2023)
This article analyzes the configuration of the agricultural territorial project in the Osa Peninsula based on the experience of associates of the oil palm cooperative OSACOOP. With a qualitative methodology, the local experience and the socioeconomic characteristics of the peasant families linked to this cooperative are analyzed to reflect on their permanence and reproduction of life in this territory. Based on the concepts of territory and territorialization processes that manifest in the productive dynamics and the particularities of this geographical space, the narratives of interviewees are taken up again to illustrate the processes of occupation, settlement and permanence of peasant agriculture in the area in which in which the cooperative is a key actor.